Conceptual modeling : 38th International Conference, ER 2019, Salvador, Brazil, November 4-7, 2019, Proceedings /: 38th International Conference, ER 2019, Salvador, Brazil, November 4-7, 2019, Proceedings. (2019) - Unknown
No abstract available